Use of Model-Based Compartmental Analysis and a Super-Child Design to Study Whole-Body Retinol Kinetics and Vitamin A Total Body Stores in Children from 3 Lower-Income Countries. Issue 2 (18th September 2019) - Ford, Jennifer Lynn; Green, Joanne Balmer; Haskell, Marjorie J; Ahmad, Shaikh M; Mazariegos Cordero, Dora Inés; Oxley, Anthony; Engle-Stone, Reina; Lietz, Georg; Green, Michael H
ABSTRACT: Background: Model-based compartmental analysis has been used to describe and quantify whole-body vitamin A metabolism and estimate total body stores (TBS) in animals and humans. Objectives: We applied compartmental modeling and a super-child design to estimate retinol kinetic parameters and TBS for young children in Bangladesh, Guatemala, and the Philippines. Methods: Children ingested [ 13 C10 ]retinyl acetate and 1 or 2 blood samples were collected from each child from 6 h to 28 d after dosing. Temporal data for fraction of dose in plasma [ 13 C10 ]retinol were modeled using WinSAAM software and a 6-component model with vitamin A intake included as weighted data. Results: Model-predicted TBS was 198, 533, and 1062 μmol for the Bangladeshi (age, 9–17 mo), Filipino (12–18 mo), and Guatemalan children (35–65 mo). Retinol kinetics were similar for Filipino and Guatemalan groups and generally faster for Bangladeshi children, although fractional transfer of plasma retinol to a larger exchangeable storage pool was the same for the 3 groups. Recycling to plasma from that pool was ∼2.5 times faster in the Bangladeshi children compared with the other groups and the recycling number was 2–3 times greater. Differences in kinetics between groups are likely related to differences in vitamin A stores and intakes (geometric means: 352, 727, and 764 μg retinol activity equivalents/d for the Bangladeshi, Filipino, and Guatemalan children, respectively). Conclusions: By collecting 1 or 2 blood samples from each child to generate a composite plasma tracer data set with a minimum of 5 children/time, group TBS and retinol kinetics can be estimated in children by compartmental analysis; inclusion of vitamin A intake data increases confidence in model predictions. The super-child modeling approach is an effective technique for comparing vitamin A status among children from different populations. These trials were registered at www.clinicaltrials.gov as NCT03000543 (Bangladesh), NCT03345147 (Guatemala), and NCT03030339 (Philippines).